Teaching Demographic Ignorance with the Correcting Misperceptions Exercise: A Replication and Extension of Previous Research - Daniel Herda (Numeracy, 2019)
Existing research from the social sciences indicates that misperceptions about immigrants are pervasive in American society and present consequences for intergroup relations. The classroom may be an arena in which to reduce this incorrectness. The current note provides a replication and extension of previous research on the effectiveness of the Correcting Misperceptions Exercise (CME) ─ an in-class demographic guessing game in which students provide their perceptions of some demographic reality and compare it to an objective data source. This analysis builds upon earlier work by 1) considering immigrants as a new demographic category of focus; 2) simultaneously analyzing cardinal misperceptions of the immigrant population size (population innumeracy) and ordinal mischaracterizations of immigrants’ most common country of origin; and 3) by comparing low-tech and high-tech versions of the CME. Perceptions measured during the game are compared to those measured in a post-test occurring three weeks later. Results indicate that participation in the game improves both types of misperceptions. However, they technology-based CME utilizing student response systems (Socrative) does not provide any additional purchase beyond a low-tech, paper-and-pencil delivery.